Yesus di Padang Gurun - Jacobs, Tom (Jurnal Orientasi Baru, 2008)
"Then Jesus was led by the Spirit into the desert to be tempted" (Mt 4:1). Jesus was tempted; not to do evil, but to mis-understand His task and mission. So His reaction to the temptation was not only a total obedience to God, but a deep spiritual, even mystic understanding of his God-given task. In this sense the desert-experience was a deepening of the vocation of Baptism. It was a water-shed, that separated Him from John the Baptist. Originally "]esus came from Galilee to the Jordan to be baptized by John" (Mt 3:13). According to the Fourth Gospel He even participated in the baptismal movement. But after His desert-experience He went His own way, leaving John and his movement behind Him. His experience in baptism and "temptation" was fundamental and became the basic inspiration for His life and work. Therefore it is not too surprising that the primitive community turned back to this basic experience. Although Jesus did not baptize, they made baptism the basic act of initiation. They did not go back to John's baptism, which was a baptism with water, but to Jesus' baptism by John as the start of a new life in Christ.